The exploitation of soil organic phosphate by grassland plants - Carroll, Nyree-Dawn (Trinity College (Dublin, Ireland). Department of Botany, 2002)
This study was concerned with the availability of soil organic phosphate (Po) to plants. To address this issue semi-natural Irish grassland soils and plants were used. Greenhouse experiments were carried out in which soil was amended with inositol hexaphosphate (IHP), a prominent soil Po compound. To maintain a natural growth environment for the plant, the indigenous microbial population of the soil was retained. Several factors, vesicular arbuscular mycorrhizae, soil bacterial and phosphatase enzymes, which can influence P nutrition of plants were examined. In addition the influence of soil N levels on the Po use of plants was determined. Nuclear magnetic resonance was used to examine the range of Po compounds in this soil. Traditional wet chemical analysis was used to measure soil phosphate levels and plant growth was followed by biomass and P accumulation data. Among the methods employed in the course of this work were quantification of soil bacteria and root infection by VAM fungi. Assays for determination of the activity of a range of soil phosphatase enzymes were performed. IHP was an available some of P for plants that could be accessed by VAM hyphae for transport to plants. The Po concentration in the soil did not affect the extent of infection of roots by VAM fungi and these fungi were beneficial to plant growth at low soil P concentrations. Streptomycin sensitive bacteria in soil were not involved in the hydrolysis of Po for plant use. Root acidic monoesterase was indicated as being the most important phosphatase enzyme for IHP breakdown to orthophosphate. Addition of N to the soil increased the potential for plant growth and the need for Po breakdown by the root acidic monoesterase. A group of Po compounds (monoester P, diester P, inorganic orthophosphate, pyrophosphate and teichoic acid) was detected in soil extracts by the technique of NMR.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin